Development of Multimedia Bilingual Learning for Early Childhood Education - Yoning Eka Pangestuni; Eny Enawaty; Indri Astuti (Universitas Muhammadiyah Enrekang, 2022)
This study aims to describe bilingual learning in PAUD Group B in TK Perintis II Arang Limbung, Sungai Raya District. The method used in this study is the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of this study were the Head of Pioneer II Kindergarten, class teachers, student behavior, and parents. Data collection techniques use interviews, observations, and documentation. Data analysis techniques through qualitative analysis. The results showed that every child can develop language naturally. However, language development is also influenced by parents, the environment, and the world of education, especially in bilingual learning, namely Indonesian and English. Students have been taught in two languages and delivered through singing, playing, and dancing. This attracts students to follow the lesson with a feeling of love and joy. Therefore, the purpose of this study is to develop English learning media so that children's cognitive abilities can be improved. The conclusions of this program study show that the bilingual program in ECCE provides positive results for children's language development.